Control of a community outbreak of hepatitis A in an area of low endemicity, Wales, 2016. Issue 10 (3rd October 2017) - Vaz, J.; Floyd, C.; Mason, B.; Shankar, A. G.; Lewis, H.
ABSTRACT: Incidence of hepatitis A in Wales is low (average of 0.48/100, 000 inhabitants from 2004–2015). We describe a community outbreak of hepatitis A involving 3 schools (primary and secondary) in South Wales between March and June 2016 and reflect on the adequacy of the control measures used. Anyone in South Wales epidemiologically linked to a serological and/or RNA positive confirmed case of hepatitis A during the 15–50 d before onset of symptoms (diarrhea, vomiting, fever, nausea, AND jaundice, or jaundice-associated symptom) was defined as a case. Case identification was based on laboratory or GP suspicion notification, changing to active surveillance toward the end. As per national guidance, household contacts were identified and offered immunisation while in schools vaccination followed evidence of transmission. We went beyond guidance by vaccinating street play mates and in secondary schools. Mass vaccination uptake was calculated. There were 17 cases, mostly in children under 16 y of age. All cases had an epidemiological link to either a school or a household case (except primary) and no travel history. Street playing was the only epidemiological link between 2 cases in different schools. A total of 139 household contacts were identified. All schools, including secondary one, had a transmission event preceding mass vaccination (overall uptake 85%, reaching 1, 574 individuals) and no tertiary cases emerged after the campaigns. We recommend extending guidance to include actions taken that helped curb this outbreak: 1) vaccinating in secondary school and 2) broadening the household contact definition. Based on our learning we further suggest 3) vaccinating upon identification of a single case who attended school while infectious regardless of source and 4) active case finding by serologically testing contacts.